Phytochemical Analysis of the Flower Buds, Pedicels and Leaves of Syzygium aromaticum (L.) Merril and Perry - Rajalekshmy, V. S.; Manimekalai, V. (Technological Innovation in Pharmaceutical Research Vol. 5, 2021)
The present study aimed to analyze the major chemical components in the flower buds, pedicels and leaves of Syzygium aromaticum by Gas-Chromatography Mass spectrometry technique. The major constituent is eugenol in all of pedicels (79.75%), buds (74.12%) and leaves (51.03%). In addition to eugenol, other important components are Acetyleugenol, Caryophyllene, Humulene, Caryophyllene oxide. Eugenol has a wide range of medicinal value such as antibacterial, antifungal, antiviral, anti-cancerous, anti-diabetic, anesthetic and antioxidant activities.